O processo de aprendizagem gerencial sobre sucessão em propriedades rurais familiares: um estudo na região de abrangência da UFFS campus de Cerro Largo/RS - Kapelinski, Fabiano (2021)
The field of managerial learning emerged to fill a gap between theory and practice in education and management development, seeking to understand the content, forms, limits and potentialities that a manager faces in his work routine. This field manifests itself in all organizational types, as well as in the administration of rural properties, especially in the stage of family succession, as it is considered one of the critical and complex points of effectiveness of the successor in the management of resources on behalf of the owner family, whose complexity lies mainly in the managerial capacity of the successor, in the reconciliation of family interests and in an intense systematic effort to continuously produce better performance indicators for the enterprise. In view of this, the present dissertation has as general objective to understand the process of managerial learning in family succession in rural properties from the perspective of graduates of the Bachelor's courses in Administration and Agronomy at UFFS campus in Cerro Largo / RS. The choice of courses was due to the fact that they have a pedagogical proposal to reverse the trend of rural migration of the young population, enable better quality of life indicators and offer new qualification opportunities to recover the economic dynamism of family farms in the region. In methodological terms, in a research of an applied nature and developed at the exploratory and descriptive levels, a qualitative approach was used to interpret the data collected through the interpretative view. The research strategy was field research. The subjects investigated were two graduates from each undergraduate course (Administration and Agronomy) at the Cerro Largo campus of the Federal University of Fronteira Sul (UFFS. Data collection was performed through semi-structured interviews and systematic integrative review. Data analysis was performed using the content analysis method and the categorical analysis technique. The results showed that managerial learning contents arise from four dimensions: individual, work, organizational and contextual. The forms of learning occur in a formal and informal way. The main difficulties pointed out by the graduates in family succession were the parents' resistance to the new ideas proposed by them, the acceptance and recognition of the successor's knowledge. The elements that enhanced managerial learning were the knowledge generated and disseminated on the rural property with formal learning from academic training, which empowered successors to acquire managerial skills and competences. The practical contribution of the study resides in the factor that only qualified academic training is not enough for the successor student of rural properties, requiring greater practical experience at the University in combination with the activities carried out on a rural property, from which the suggestion is derived. UFFS to include more teaching activities in the internships. It was possible to verify whether basic commitments of the University, as well as of the two courses are being achieved, such as the promotion of regional development and family farming, which allows for a self-assessment and the articulation of public policies, through the experience defended in this work. The study provided an understanding of the managerial learning process, in the family succession of rural properties, regarding the contents, forms, limits and potentialities, in addition to providing UFFS with an overview of the graduates on the research theme of this dissertation, in which is related to teaching methodologies at the University.